LEGAL EXPLANATION (RESTATEMENT) OF THE CONCEPT OF GOVERNMENT ADMINISTRATIVE ACTIONS ACCORDING TO LAW NO. 30 OF 2014 CONCERNING GOVERNMENT ADMINISTRATION - Bimasakti, Muhammad Adiguna (Jurnal Hukum dan Peradilan, 2022)
Law No. 30 of 2014 concerning Government Administration (UU AP) stipulates two types of Administrative Actions, namely Government Decrees and Government Administrative Actions. In judicial practice in the administrative courts, the term Government Administrative Action is often interpreted differently from the concept of Real Action. This study aims to determine the concept of Government Administrative Action according to Law No. 30 of 2014 concerning Government Administration. The writing method used in this research is normative juridical method using statutory approach and conceptual approach. The results of the study show that the concept of "Government Administrative Action" in Article 1 point 8 of the UU AP can be interpreted grammatically, historically and systematically as Real Action as referred to in Article 87 letter a of the UU AP. The jurisdiction for administrative dispute where the objects are â€œreal actâ€ (government administrative action) and â€œwritten decisionâ€ (government decrees) lays on administrative court, where as for other legal acts which cannot be classified as real act (government administrative action) or written decision (government decrees) lays on the general court as residual jurisdiction (resrechter).